Security Issues in Mobile Ad Hoc Networks. (7th November 2012) - Sandoval Orozco, A. L.; García Matesanz, J.; García Villalba, L. J.; Márquez Díaz, J. D.; Kim, T.-H.
Abstract : Ad hoc networks are built on the basis of a communication without infrastructure and major investigations have focused on the routing and autoconfiguration problems. However, there is a little progress in solving the secure autoconfiguration problems in mobile ad hoc networks (MANETs), which has led to the proliferation of threats given the vulnerabilities of MANETs. It is clear that ad hoc networks have no centralized mechanism for defense against threats, such as a firewall, an intrusion detection system, or a proxy. Therefore, it is necessary that the defense of interests of each of the ad hoc components is the responsibility of each member node. This paper shows the most common threats to ad hoc networks and reviews several proposals that attempt to minimize some of these threats, showing their protection ability and vulnerabilities in light of the threats that might arise.